The incremental validity of a computerised assessment added to clinical rating scales to differentiate adult ADHD from autism spectrum disorder - Groom, Madeleine J.; Young, Zoe; Hall, Charlotte L.; Gillott, Alinda; Hollis, Chris (Elsevier, 2016)
There is a clinical need for objective evidence-based measures that are sensitive and specific to ADHD when compared with other neurodevelopmental disorders. This study evaluated the incremental validity of adding an objective measure of activity and computerised cognitive assessment to clinical rating scales to differentiate adult ADHD from Autism spectrum disorders (ASD). Adults with ADHD (n=33) or ASD (n=25) performed the QbTest, comprising a Continuous Performance Test with motion-tracker to record physical activity. QbTest parameters measuring inattention, impulsivity and hyperactivity were combined to provide a summary score (‘QbTotal’). Binary stepwise logistic regression measured the probability of assignment to the ADHD or ASD group based on scores on the Conners Adult ADHD Rating Scale–subscale E (CAARS-E) and Autism Quotient (AQ10) in the first step and then QbTotal added in the second step. The model fit was significant at step 1 (CAARS-E, AQ10) with good group classification accuracy. These predictors were retained and QbTotal was added, resulting in a significant improvement in model fit and group classification accuracy. All predictors were significant. ROC curves indicated superior specificity of QbTotal. The findings present preliminary evidence that adding QbTest to clinical rating scales may improve the differentiation of ADHD and ASD in adults.